Peran Kepercayaan Sosial dan Sentralitas Jaringan Terhadap Persepsi Resiko Bencana Alam - Sapta Widi Wusana; Rahmat Hidayat (Universitas Andalas, 2017)
This research is aimed to understand the risk perception of Merapi disaster in hazardous community, by viewing the contribution of social network centrality and social trust towards risk perception of natural disaster. Hypotheses in this research are; social network centrality (degree, closeness, betweenness, eigenvector centrality) and social trust which all together are able to predict Merapi’s disaster risk perception. This research was conducted at Dusun Gondoarum, Desa Wonokerto, Kecamatan Turi, Kabupaten Sleman, DIY, with 83 total respondents, research data revealed by psychological scale and name generator. Result of this research prove that social trust, centrality degree, centrality betweeness, centrality closeness, and centrality eigenvector all together are able to predict merapi’s disaster risk perception, with 30.9 % coefficient determination value (R2). Which mean that the research hypothesis is convicted. Two predictor which gave a big role towards natural disaster risk perception are social trust and eigenvector centrality with coefficient determination at 23.6%.